Judicial System in the Islamic Judicial Heritage in the Malay World: The Study of Tsamarat al-Muhimmah, Written by Raja Ali Haji - Bintania, Aris; Setyadiharja, Rendra; Mawazi, Abd. Rahman (PERADA, 2024)
This article examines the study of qadha fiqh in the judicial system that was in the Malay world, especially in the kingdoms of Johor, Pahang, Terengganu, Riau-Lingga, by reviewing the book Tsamarat al-Muhimmah by Raji Ali Haji. This study is divided into two main discussions: the legal and judicial systems in the kingdom. It is known that royal law, its legal system applies, which refers to Islamic law (shari'a). Whereas the justice system refers to fiqh qadha as contained in the fiqh study, which contains the meaning of the court, the composition of the judicial officials' functions and duties, the source of applicable law is Islamic law based on the Qur'an and Hadith, etiquette and ethics of judicial officials, procedures for deliberating officials adjudication, procedures for settling differences of opinion among judges (qadi), decision making (law) is carried out after the examination is complete. All conditions are fulfilled, Qadi al-Qudat as the leader of the qadi, must appoint a judge who has the appropriate expertise in examining cases, prohibit the Qadi from accepting gifts (gratifications), the procedures for selecting judicial officials and the criteria, the oath of allegiance to the appointment of judicial officials. This indicates the need for a judicial institution that is legally valid, and its officials must have ethical values so they can make decisions in accordance with the Shari'ah and the laws that apply in the kingdom.